Highly efficient Michael additions of acrylonitrile with alcohols over K2CO3/zeolite catalysts in a solvent‐free system. (1st November 2020) - Zhan, Hongju; Zhao, Lin; Xia, Qinghua; Zhou, Dan; Ma, Xuetao; Lu, Xinhuan
Abstract : The supported base/zeolite catalysts are prepared and applied in the catalytic Michael additions of acrylonitrile with monohydric alcohols to 3‐alkoxypropanenitriles in a solvent‐free system. The catalysts are characterised by powder X‐ray diffraction. For the Michael addition of methanol to acrylonitrile, 10% K2 CO3 /ZSM‐5 shows the best activity with 98.3 mol% conversion of acrylonitrile and 100% selectivity of 3‐methoxypropanenitrile. The recyclable stability of the 10% K2 CO3 /ZSM‐5 catalyst is confirmed. The effects of various parameters are investigated systematically. By comparing the catalytic activity of anion‐exchanged CO3 2− ‐resin for the titled addition, a feasible reaction route is proposed.